Sobre la partícula «rai» i els tòpics - Solà i Pujols, Jaume (Caplletra. Revista Internacional de Filologia, 2015)
In the first part of the paper, I characterize the particle "rai", used in some dialects of Catalan, as a topicemphasizer (by topic I mean left-dislocated constituent). In the second part I use this particle as a criterion to identify the class of topics, and I speculate on the nature of this class, which is in complementary distribution with the class of operators.